Association between CYP2C19 polymorphism and proton pump inhibitors adverse drug reactions: a narrative review - Ibrahim, Asmaa; Yusuff, Kazeem; Awaisu, Ahmed; Elewa, Hazem (Frontiers in Pharmacology, 2025)
Proton pump inhibitors (PPIs) are widely prescribed medications for the management of acid-related disorders, due to their effectiveness and favorable pharmacokinetics. However, the occurrence and severity of adverse drug reactions (ADRs) in patients using PPIs, particularly in relation to their association with CYP2C19 polymorphisms, are of great concern. This association has largely been investigated through observational studies, which have shown conflicting or weak findings. Therefore, this review aims to examine the current evidence regarding the long-term ADRs of PPIs and their link to CYP2C19 variants.